Ellipsoid-shaped copper oxide as an effective peroxymonosulfate activator for perfluorooctanoic acid decomposition. (March 2023) - Singh, Seema; Patidar, Ritesh; Srivastava, Vimal Chandra; Kumar, Praveen; Singh, Ajay; Lo, Shang-Lien
Abstract: In the present study, ellipsoid-shaped cupric oxide (CuO) with uniform size were synthesized by facile template-free urea-glycerol-assisted hydrothermal approach and consequent heat treatment. The CuO nanospheres possessed tunable pore features with comparatively higher value of a specific surface area (98.4 m 2 g −1 ) and an excellent number of pores size 9.8–12.3 nm. As prepared catalysts exhibited excellent peroxymonosulfate (PMS) activation ability for the treatment of highly toxic perﬂuorooctanoic acid (PFOA) from aqueous solution. Moreover, a systematic degradation approach was investigated by the study of various operating parameters such as PMS dose, catalyst dose, concentration of PFOA, initial pH, and temperature. Zeta potential measurement confirmed that PMS activation with ellipsoid CuO enhanced the availability of more active Lewis acid sites and show high chemical stability. About 92% PFOA degradation and 78% TOC reduction were achieved within 90 and 120 min respectively at optimum condition of initial pH= 7, catalyst dosage = 0.5 g L −1, PMSo = 0.5 mM, and temperature= 328 K for a solution of PFOAo = 10 mgL −1 by PMS/ellipsoid CuO system. Scavengers test analysis confirmed that singlet oxygen ( 1 O2 ) is the most active species which effectively participated in the strong oxidative-reductive mechanism of PFOA degradation. In addition, a two-step pseudo-first-order kinetic model was well fitted, and very little metal leaching was observed via reusing after six cycles. GC-MS analysis was used for identification of the intermediates, a possible stepwise degradation pathway of long-chain perfluorosulphonic acids (PFACs) to shorter chain intermediates with the role of ellipsoid-CuO in PMS activation has been proposed. Graphical Abstract: ga1 Highlights: Positive surface of ellipsoid-CuO in PMS activation facilitate the Cu + /Cu 2+ cycling. PMS activation promotes the radical and non-radical oxidative-reductive reactions. Radical-induced (SO4 − and OH) and non-radical ( 1 O2 ) are the key active species. Acidic pH promotes the Lewis acid-base interaction. Long chain PFOA was mineralized via the short chain intermediates to F − and CO2 .